Meanings and feeding practices in a seniors diabetic group and their families, in the Cantón of La Unión - Sedó Masís, Patricia (2005)
Using social phenomenology, the results of a qualitative study of food habits and their significance for a group  of elderly persons with diabetes mellitus (PAMD) and their families in el Canton de La Unión, in Cartago, are presented in this article. The PADM commonly had low income, poor educational level, low access to health care in health centers, low participation in other related activities to medical advice, and nutritional information based on the prohibition of eating certain foods. The foods that were thought as prohibited were associated with traditions, the expression of affection, the act of living together and social recognition. It is important to highlight the expectative that others should indicate the PAMD what they should eat. This attitude reflects greater dependency and loose of autonomy. In addition, the role of careers and supervisors of the diet recommended by the health center is assigned to family members, especially women, despite the fact that the family of the elderly person rarely accompanied him/her to health care and educational activities.